Realisasi Peningkatan Kesejahteraan Masyarakat Melalui Implementasi Program Bantuan Stimulan Perumahan Swadaya (BSPS) dalam Mengurangi Kuantitas dan Kualitas Rumah Tidak Layak Huni (RTLH) - Seri Mughni Sulubara; T. Saiful Basri; Zulfa Zainuddin; Riska Riska (Lembaga Pengembangan Kinerja Dosen, 2025)
The Self-Help Housing Stimulant Assistance Program (BSPS) emerged as a response to the housing and settlement problems faced by the Indonesian people, especially related to the low quality of life due to slums (Sitompul, 2022). This program aims to provide livable houses for low-income people (MBR) through stimulant government assistance (Seri Mughni Sulubara, 2024). The research method used is a qualitative descriptive research method. This method aims to make descriptions of data systematically, factually, and accurately about existing facts. Descriptive research that is carried out continuously on the object of research is called a continuous descriptive method. The results of activities or findings from the implementation of the Self-Help Housing Stimulant Assistance Program (BSPS) in reducing the quantity and quality of Uninhabitable Homes (RTLH) show that this program has a positive impact on the beneficiary community. The BSPS program succeeded in improving the quality of the beneficiaries' houses. Houses that were built or renovated have a solid structure, adequate area, and a livable level of safety (Seri Mughni Sulubara, Amrizal Amrizal, et al., 2024). By making home improvements, BSPS contributes to reducing the number of uninhabitable houses and creating a more decent environment (B & Sadriah, 2020).